(untitled) (Research, Society and Development, 2020)
The correct disposal of chemotherapeutic drugs requires specific care and, if it is not being carried out within its safety criteria, it can cause the compromise of natural resources, such as water and soil contamination, which can impact public health. The purpose of this article is to demonstrate, through reports from employees of the organization, and the data provided by that company, the processes and methods for disposal, handling, storage, distribution of the various types of chemotherapy. The case study was used together with an exploratory research of qualitative character, for the collection and analysis of data that aims to solve the problems presented in Hospital Logistics and Reverse Logistics Management of a private hospital located in São Paulo. It can be seen, among the problems, that the loss rate stipulated by the hospital analyzed for this type of medication would be on average 2 to 3% of its stock. And among the suggested proposals, the creation of a unit for specific treatment of cancer patients in which the use of chemotherapy drugs will be centralized, avoiding losses and errors in dosage.